Characterization for crystallization of SrBi2Nb2O9 thin films on Si substrates - Yoo, DC; Lee, JY; Sinclair, R; Kim, IS; Kim, YT (KOREAN PHYSICAL SOC, 2003)
Ferroelectric layered-perovskite SrBi2Nb2O9 (SBN) thin films have been deposited on Si (100) substrates by metalorganic decomposition method. The crystallization process of the SBN thin films post-annealed under various temperature conditions was investigated using transmission electron microscopy (TEM). The SBN thin films annealed up to 600 degreesC had a fluorite-like phase and had nano-sized round grains. High resolution TEM study revealed that the fluorite-like phase was cubic Bi2O3. However, the SBN thin film annealed at 700 degreesC had a layered-perovskite SBN phase with very large grains about 0.2 - 0.3 mum. It was found that these large grains originated from the agglomeration of the small round grains having similar orientations rather than from the growth of small grains.
Keywords: FERROELECTRIC CAPACITORS; SRBI2TA2O9; FATIGUE; GROWTH